Lip Service Presiden Jokowi: Politisasi Wacana Demokrasi dan Antikorupsi - Putri Arthadea Khansa; Esti Junining; Oni Dwi Arianto; Agus Wahyudi; Andik Yuliyanto; Ervan Kus Indarto; Rima Firdaus (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
Communication requires attention to honesty and trust. Communicators must have credibility that can be trusted. The speech will be rewarded if it matches the action. The discrepancy between speech and implementation action will only make a speech as lip service. This research aims to identify lip service from President Jokowi and reveal its context. This intertwined reading of the text and context will provide a comprehensive understanding of President Jokowi's lip service communication as well as an understanding of why this lip service communication occurred. This research uses the Political Discourse Analysis (PDA) method. PDA method analyzes Jokowi's lip service texts and contexts: the permissibility of demonstrations, KPK law revision, call for more criticism, and TWK for KPK employees. It has been observed that President Jokowi engages in lip service communication when the topic of discussion revolves around two key discourses: fundamental democratic values and anti-corruption measures. The research findings suggest that such communication is employed to politicize these discourses and maintain President Jokowi's image as a democratic and anti-corruption leader